Cross-cultural considerations: mentoring teachers in Jewish day schools. Issue 1 (1st January 2021) - Efron, Efrat Sara; Winter, Jeffrey S.; Bressman, Sherri
ABSTRACT: This study focuses on the impact of mentoring in Jewish day schools through the lens of cross-cultural considerations. The researchers examined the influence of differences in culture and religion on mentoring relationships and professional growth experiences. Findings indicate that building bridges of understanding and trust in a cross-cultural mentoring environment, requires the viewing of teacher mentoring as context-specific. Mentoring is strengthened when mentors become familiar with the school community and exhibit a respectful, and non-judgmental attitude toward the unique religious and cultural elements of the school community. Findings from the study provide an important contribution to discourse about teacher mentoring through a new and unique lens that focuses on cross-cultural relationships and their potential to enhance professional development and learning opportunities for teachers and mentors.